Motivations to Study Abroad: A Case Study of the College of Agricultural and Life Sciences Agribusiness Short-Term Study Abroad Program - Amber Lynn Beseli; Wendy J Warner; Barbara M Kirby; David W Jones (Journal of International Agricultural and Extension Education, 2016)
The purpose of this study was to gain a better understanding of the student participants’ motivations to partake ina short-term study abroad experience. This was an observational case study of the North Carolina StateUniversity College of Agricultural and Life Sciences Agribusiness Short-Term Study Abroad Program with the 2014 program student participants. The study explored student participants’ motivations to participate in a short-term study abroad program. This study found students were motivated to participate in a short-term study abroad program because of the short-term length aspect, the completion of course credits, and encouragement from other people, both other students and faculty
Keywords: Study abroad; Short-term study abroad; Student Motivations; International Experiences